INCREASING VISUAL IMPACT IN MSME STUDY CASE: KUE GIPANG TIGA BUNDA - Alrazi, Camila Zahra; Rachman, Anung (ARTISTIC : International Journal of Creation and Innovation, 2023)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are vital for Indonesia's economic growth, specifically in promoting local products. However, numerous MSMEs in Cilegon face difficulties due to an absence of robust visual branding. Accordingly, this study seeks to explore the influence of visual branding on MSMEs in Cilegon, with a specific focus on Kue Gipang Tiga Bunda by applying design thinking approach. Creating a strong brand identity requires the use of visual branding elements such as logos and key visuals. The objective of this research is to develop a distinct brand identity for Kue Gipang Tiga Bunda to set them apart from competitors and enhance brand awareness. Branding may improve brand recognition, attract customers, and facilitate MSME expansions, thereby promoting Cilegon's socio-economic development and competitiveness in the tourism industry.